Análisis e interpretación de los estados financieros de Hormiconstrucciones cia. Ltda. Periodo 2011- 2012 - Muñoz León, María Fernanda (2016)
This thesis called "ANALYSIS AND INTERPRETATION OF FINANCIAL STATEMENTS HORMICONSTRUCCIONES CIA. LTDA. PERIOD 2011 - 2012 "was conducted taking into account each of the phases of the research process and has also complied with the development and presentation of the work available to the Academic Regime Regulations of the National University of Loja. Compliance given to the objectives through the collection of information regarding the current financial situation through the Financial Statements of the years 2011-2012, then a vertical analysis was performed to analyze each of the ledger accounts with the group to that belong; likewise a comparative analysis was performed to determine the variation of the items at different times; also it proceeded to establish consistent financial reasons to the activity of the company in order to meet its liquidity, activity, indebtedness and profitability; concluding with the presentation of the report, which was released the results regarding the analysis and interpretation made to the financial statements. Influential in decision-making in the short and long term. The results obtained after the applied financial analysis show that the company presents a slight decrease in 2012 in relation to the solvency ratio, with respect to liquidity Hormiconstrucciones Cia. Ltda., Has a relatively low working capital in the last period, and; in relation to the equity debt is high because it is committed by excessive debt in 2011; which it is why we face this reality is recommended that the accountant of the Company perform a financial analysis once a year, in order that managers can assess the financial and operational performance of the entity managing to obtain a clear view of the situation Real it held by the company and thus employ the necessary corrective measures aimed at the smooth development of the company.